Meningkatkan Kemampuan Membaca Permulaan Melalui Metode Orton Gillingham bagi Peserta Didik Disabilitas Intelektual Ringan (Single Subject Research Kelas VI di SLB Serasi Payakumbuh) - Zulfarahmi, Vivi; Zulmiyetri, Zulmiyetri; Sopandi, Asep Ahmad; Arnez, Gaby; Yuliana, Syari (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research began from a problem experienced by a sixth-grade student with mild intellectual disabilities who was unable to read at the beginning level, especially words with the KV-KVK pattern. The student could only read KV syllables and KV-KV patterned words. To address this issue, the Orton Gillingham method was used, which has been proven to enhance early reading skills. This study aims to improve beginning reading abilities through the Orton Gillingham method for students with mild intellectual disabilities. This research used a quantitative approach with a Single Subject Research (SSR) design of the A-B type. The subject was one student with mild intellectual disability. The independent variable was the Orton-Gillingham method, while the dependent variable was the student's early reading ability. Data were collected through tests and analyzed visually using graphs. The results showed an improvement from 30% during the baseline phase (three sessions) to 100% by the end of the intervention phase (seven sessions). Thus, the Orton-Gillingham method was effective in improving early reading skills in a student with mild intellectual